Assessing the uses of 230Th, 232Th and 231Pa as proxies in the past and modern ocean - Deng, F (2014)
Thorium-230 and protactinium-231 have been widely used as proxies of oceanic processes in both modern and past marine environment. Their application as such proxies is, however, limited by sparse data from the modern ocean with which to characterize their distribution and behavior. This thesis aims to provide such data and to assess their uses as oceanic proxies for ocean circulation, sediment dissolution, and modern dust input. Twelve profiles of dissolved 230Th, 231Pa and 232Th obtained on a meridional GEOTRACES section in the Southwest Atlantic confirm the expected transport and fractionation of 231Pa from 230Th by deep ocean circulation out of the modern Atlantic. There is however neither a water mass dependence nor progressive change as water masses age, which challenges the use of sedimentary 231Pa/230Th to assess past flow in the South Atlantic. Decreases of 230Th and 231Pa observed in near-bottom water indicate enhanced sea-floor removal in regions where nepheloid layers are present. In a second study of sedimentary nuclides concentration, high-resolution 230Thxs profiles from sediment in Southeast Atlantic exhibit increasing 230Thxs concentrations from core-top to a depth of ∼3 cm followed by relatively constant values at greater depth, suggestive of sediment dissolution in the upper sediment core. This observation suggests the use of 230Thxs to quantify sediment dissolution. Combined with sediment composition measurements, 230Thxs also provides an assessment of which constituents are dissolving from the sediment. (231Pa/230Th)xs ratios do not appear to be affected by sediment dissolution. A third study, in the tropical Atlantic Ocean, combines water-column measurements of 230Th, 232Th with coeval aerosol measurements, and allows assessment and improvement of the use of 232Th to quantify dust input to the surface ocean. 232Th-derived dust flux increases from 0.43 g/m2/yr at low latitude in the South Atlantic to 10.70 g/m2/yr at higher latitude in the North Atlantic, and broadly agree with a model of dust input. The data presented in this thesis have expanded the dataset of 230Th, 232Th and 231Pa in the Atlantic Ocean, and provide an insight into future uses of these nuclides as oceanic proxies.